Transcriptomic and metabolomic analyses of Tartary buckwheat roots during cadmium stress - Hanmei Du; Lu Tan; Changhe Wei; Shengchun Li; Zhou Xu; Qinghai Wang; Qiuzhu Yu; Peter R. Ryan; Hongyou Li; An’hu Wang (Scientific Reports)
Abstract Cadmium (Cd) can adversely damage plant growth. Therefore, understanding the control molecular mechanisms of Cd accumulation will benefit the development of strategies to reduce Cd accumulation in plants. This study performed transcriptomic and metabolomic analyses on the roots of a Cd-tolerant Tartary buckwheat cultivar following 0 h (CK), 6 h (T1), and 48 h (T2) of Cd treatment. The fresh weight and root length were not significantly inhibited under the T1 treatment but they were in the T2 treatment. The root’s ultrastructure was seriously damaged in T2 but not in T1 treatment. This was evidenced by deformed cell walls, altered shape and number of organelles. A total of 449, 999 differentially expressed genes (DEGs) and eight, 37 differentially expressed metabolites (DEMs) were identified in the CK versus T1 and CK versus T2 comparison, respectively. DEGs analysis found that the expression of genes related to cell wall function, glutathione (GSH) metabolism, and phenylpropanoid biosynthesis changed significantly during Cd stress. Several WRKY, MYB, ERF, and bHLH transcription factors and transporters also responded to Cd treatment. Our results indicate that Cd stress affects cell wall function and GSH metabolism and that changes in these pathways might contribute to mechanisms of Cd tolerance in Tartary buckwheat.